Depression in male patients on methadone maintenance therapy - Baharudin, Azlin; Mislan, Noormazita; Ibrahim, Normala; Sidi, Hatta; Nik Jaafar, Nik Ruzyanei (Wiley, 2013)
Introduction Depression is one of the most common psychiatric conditions in men. The aim of the study was to determine the depressive symptoms and associated factors among men on methadone maintenance therapy (MMT).